Profile of Morris Moscovitch - Sarah C. P. Williams (Proceedings of the National Academy of Sciences, 2026)
Morris Moscovitch’s five-decade career has reshaped scientists’ understanding of how the brain stores and retrieves memories. His Multiple Trace Theory challenged the view that the hippocampus serves only as temporary storage, showing instead that richly detailed episodic memories remain dependent on the hippocampus indefinitely. Moscovitch demonstrated that the hippocampus contributes not just to remembering but to imagination, problem-solving, and social cognition. His recent work reveals that people detect episodic richness in others’ memories and use this signal to guide social preferences. Through collaborative research spanning hemispheric specialization and face recognition, Moscovitch has revealed memory as central to human cognition.